Efek Tunjangan, Insentif dan Kedisiplinan Sebagai Determinan Kinerja Karyawan - Herman Sjahruddin; Arie Nurhidayat Anisyar (Universitas Islam Kadiri, 2021)
Competition between banks requires banks to maximize the performance of their employees. This study explores the effects of allowances, incentives, and discipline as determinants of performance. Data collection uses primary data obtained through questionnaires. A total of 39 employees of PT. Bank BRI (Persero), Tbk Sungguminasa Branch was used as the sample. Multiple regression analysis through SPSS 25.0 software was used to analyze the data. The empirical results show that the low allowances given in its implementation can improve employee performance. Another causality is proven if high incentives are given to employees and high discipline is proven to improve employee performance